Successful anesthetic management for microsurgical excision of ruptured cerebellar arteriovenous malformation with trapped endovascular microcatheter - Redhu, Shruti (Medknow Publications & Media Pvt Ltd, 2014)
Microsurgical excision and good anesthetic management of arteriovenous malformation (AVM) that ruptures during endovascular embolization can ensure good outcome despite per-procedural catastrophe. This case report illustrates the successful anesthetic management of microsurgical excision of ruptured AVM with entrapped microcatheter and highlights the role of the anesthesiologist in careful monitoring of the patient's hemodynamic status and communicating any changes to the radiology team to facilitate check angiography to diagnose the intracranial complication. This case highlights the need for anticipating and defining a catastrophe plan in advance of each interventional neuroradiology procedure as complications are rapid and require good multidisciplinary communication to ensure safe and successful outcomes.